1991
DOI: 10.1099/00221287-137-9-2223
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of extracellular lipase from Pseudomonas aeruginosa EF2

Abstract: Extracellular lipase was purified from a Tween 80-limited continuous culture of Pseudomonas aeruginosa EF2 by ultrafiltration of the culture supernatant followed by anion-exchange and gel-filtration FPLC. The lipase was composed of a single subunit (M, 29000, PI 4.9), which was capable of a variable degree of aggregation, and which exhibited both lipase activity, measured with the insoluble substrate olive oil (predominantly triolein), and esterase activity, measured with the soluble substrates p-nitrophenyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 14 publications
7
38
1
2
Order By: Relevance
“…aeruginosa PAClR (Stuer et al, 1986;Jaeger et al, 1991Jaeger et al, , 1992 and of P . aeruginosa EF2 (Gilbert et al, 1991) yielded results which correspond very well to data deduced from the nucleotide sequence of the lipase gene of P. aeruginosa PAO1. These data comprise the molecular mass of the enzyme, the isoelectric point (calculated : PI = 5.6 ; analysed by isoelectric focussing : PI = 5.8), the overall amino acid composition and the amino acid sequence of the N-terminus of the secreted protein.…”
Section: Discussionsupporting
confidence: 70%
“…aeruginosa PAClR (Stuer et al, 1986;Jaeger et al, 1991Jaeger et al, , 1992 and of P . aeruginosa EF2 (Gilbert et al, 1991) yielded results which correspond very well to data deduced from the nucleotide sequence of the lipase gene of P. aeruginosa PAO1. These data comprise the molecular mass of the enzyme, the isoelectric point (calculated : PI = 5.6 ; analysed by isoelectric focussing : PI = 5.8), the overall amino acid composition and the amino acid sequence of the N-terminus of the secreted protein.…”
Section: Discussionsupporting
confidence: 70%
“…The results of optimum working temperature for lipase are confirmed by studies done by Gilbert et al [25] showed that lipase activity decreased after 45ºC while Zaliha et al [26] found lipase activity to be optimum above 40ºC. The results for varying optimum pH coincide with various studies carried out by Mubarak-Qamsari et al [21] which reveal similar results that the enzyme has the ability to work at pH 9 and 10.…”
Section: Discussionsupporting
confidence: 79%
“…KE38 was grown at optimum at 25°C, but its lipase had maximum lipase activity at 45°C. In contrast to our results, Gilbert et al (1991) indicated that maximum lipase activity by Pseudomonas spp. was detected at 30°C, while the results reported by Qamsari et al (2011) showed that maximum lipase activity produced by P. aeruginosa KM110 was at temperature range (35 to 45°C).…”
Section: Effect Of Temperature On Lipase Activitycontrasting
confidence: 56%